IDENTIFICATION AND DIVERSITY OF ENDOPHYTIC FUNGI ASSOCIATED WITH THE SEAGRASSES OF CEBU, CENTRAL PHILIPPINES - Venus Kinamot; Alvin Monotilla (BIOTROPIA, 2023)
Endophytic fungi were poorly documented in the marine environment, especially in seagrasses regardless of their importance as sources of novel metabolites. In the Philippines, studies are dearth despite having large areas of seagrass meadows. Thus, this study was conducted to isolate and identify endophytic fungi associated with common seagrasses: Enhalus acoroides, Cymodocea serrulata, and Thalassia hemprichii from the Philippines by morphologic and molecular methods. Seven species were identified in this study: Aspergillus tamarii, A. ochraceopetaliformis, A. sydowii, Penicillium citrinum, Xylaria sp., Beauveria bassiana, and Eutypella sp. Morphologically, Aspergillus spp. had septate hyphae, biseriate conidiophore, and smooth to rough globose conidia. Penicillium had a green colony, biverticillate conidiophore, and smooth, globose conidia. Beauveria bassiana had white to cream colonies with irregular edges and a powdery appearance. The conidiogenous cells had zigzag rachis in which a chain of conidia emerged. Eutypella sp. had white, filariform, and plumose colony. Xylaria sp. had a white colony with conspicuous radial lines and a plumose margin.  Phylogenetic analysis using 80 ITS rDNA sequences by neighbor-joining revealed the clustering of our isolates with the closest match taxa in the same clade with 100% bootstrap value. The estimate of evolutionary divergence between our isolates and their closest match taxa by pairwise distance showed no nucleotide base substitution suggesting high sequence identity between sequences. The most diverse endophyte is Aspergillus as it is ubiquitously adapted to the marine environment. To our knowledge, this is the first report of these species colonizing the seagrasses from the Philippines.